Bacterial diversity in the biofilms on mariculture polystyrene foam at Xiamen’s coast - Zhang, Benjuan; Liu, Renju; Xu, Haiming; Zhao, Sufang; Wang, Jiannan; Shao, Zongze (Frontiers in Marine Science, 2024)
Expanded polystyrene (EPS), commonly used as floating material in mariculture, could be a significant source of coastal PS waste. Prolonged floating in seawater leads to the formation of dense biofilms, which could disperse into the oceanic environment and spread to water bodies even the seabed as EPS deteriorates into microplastics. To understand the bacterial community structure in EPS surface biofilms, this study employed high-throughput sequencing technology to analyze the biofilms on EPS foams used in offshore mariculture aside Xiamen. Analysis of 24 biofilm samples from different seasons revealed significant differences in bacterial community structures. However, we have identified the core groups of the EPS biofilm, including Flavobacteriaceae, Rhodobacteraceae, Halomonadaceae, Exiguobacteriaceae, Vibrionaceae, and Pseudoalteromonadaceae. The Halomonadaceae and Exiguobacteriaceae are particularly attracted to the subtropical EPS material. In addition, groups with potential of degrading PS were identified, such as Alcanivorax, Pseudomonas, Acinetobacter, Exiguobacterium, Brevundimonas, and Bacillus, as well as the potential fish pathogen Acinetobacter johnsonii. The microbial biofilms formed on floating EPS demonstrate high diversity and are strongly influenced by environmental conditions. This study contributes to a deeper understanding of the interactions of bacteria in the biofilm with widely used and dispersed floating materials in the oceans.